Development of a preclinical model of myeloid tumors with high immune checkpoints expression - D. A. Senichkina; A. I. Shakirova; O. S. Epifanovskaya; I. N. Gaponenko; T. A. Pyatiizbyantsev; E. V. Belotserkovskaya; A. B. Malyshecheva; K. V. Lepik; I. S. Moiseev (Онкогематология)
Background. Myelodysplastic syndrome is a group of malignant blood diseases with a high risk of transformation into acute myeloid leukemia. One treatment approach is to target immune checkpoints (ICs) that are overexpressed on tumor cells. To develop these drugs, relevant models are needed for highthroughput screening and study of these biologically active substances, since traditionally used models (mouse and patient biomaterials) are difficult to access, financially and laborintensive, and are characterized by poorly reproducible results.Aim. To develop a model based on a human myeloid cell line with increased expression of L1 and TIM3 to study the activity of ICs inhibitors, the presence of which in the tumor microenvironment in patients with myelodysplastic syndrome and acute myeloid leukemia was associated with a high risk and worse prognosis.Materials and methods. Initial testing of the L1 and TIM3 basal expression level was carried out on cell lines: TH1, HL60, OCIAML2, OCIAML5, KG1, MonoMac1. Induction of IC expression was carried out using interferon γ. Analysis of marker expression was carried out 24 hours after induction of ICs expression and addition of MK2206 using flow cytometry.Results. Basal expression of the studied ICs receptors was absent in all of them, except for KG1; TIM3 was present in 88.4 ± 7.1 % of cells, and L1 – in 88 ± 8.5 %. The addition of interferon γ at a concentration of 50 ng/mL to the MonoMac1 culture led to a significant increase in the proportion of TIM3 and L1 expressing cells (53.3 ± 12.2 and 97.3 ± 1.1 % respectively, compared to 0.1 ± 0.1 and 0.1 ± 0.1 % without interferon γ), and for TH1 only L1 expression (87.5 ± 20 %, control 0.1 ± 0.1 %) was observed at the concentration of interferon γ in a medium of 50 ng/mL, while the proportion of cells expressing TIM3 was 6.9 ± 10 % (control 0.1 ± 0.1 %).Conclusion. The KG1 line, which constantly expresses significant levels of target ICs, as well as TH1 and MonoMac1, which are induced by 50 ng/mL interferon γ, were selected as a model with increased L1 and TIM3 expression based on a human myeloid cell line. The model efficiency was confirmed by the rational response to the IC pathway inhibitor.